2000
DOI: 10.1128/aem.66.5.2037-2044.2000
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses to Starvation in the Marine Oligotrophic Ultramicrobacterium Sphingomonas sp. Strain RB2256

Abstract: Sphingomonas sp. strain RB2256 is representative of the ultramicrobacteria that proliferate in oligotrophic marine waters. While this class of bacteria is well adapted for growth with low concentrations of nutrients, their ability to respond to complete nutrient deprivation has not previously been investigated. In this study, we examined two-dimensional protein profiles for logarithmic and stationary-phase cells and found that protein spot intensity was regulated by up to 70-fold. A total of 72 and 177 spots s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 34 publications
5
49
0
Order By: Relevance
“…The HF diet-induced increase in spectral abundance factors related to category J (translation) may reflect adaptation of microbial cells to meet their needs for survival in a milieu with low energy originating from carbohydrates. For example, in vitro studies showed that levels of protein synthesis in marine Sphingomonas during starvation were low but preformed ribosomes and whole-cell proteins were retained for at least 7 days in culture (Fegatella and Cavicchioli, 2000). The authors proposed that in starvation, the number of ribosomes is in large excess relative to protein synthesis requirements, which may corroborate increased signals for ribosomal proteins in our HF data sets; and (ii) the depth of analysis (both in terms of biological replicates and protein annotation) is still limiting, that is, only most dominant proteins are detected, which likely prevents better discrimination of the effect of the two diets at the metaproteome level.…”
Section: Discussionmentioning
confidence: 99%
“…The HF diet-induced increase in spectral abundance factors related to category J (translation) may reflect adaptation of microbial cells to meet their needs for survival in a milieu with low energy originating from carbohydrates. For example, in vitro studies showed that levels of protein synthesis in marine Sphingomonas during starvation were low but preformed ribosomes and whole-cell proteins were retained for at least 7 days in culture (Fegatella and Cavicchioli, 2000). The authors proposed that in starvation, the number of ribosomes is in large excess relative to protein synthesis requirements, which may corroborate increased signals for ribosomal proteins in our HF data sets; and (ii) the depth of analysis (both in terms of biological replicates and protein annotation) is still limiting, that is, only most dominant proteins are detected, which likely prevents better discrimination of the effect of the two diets at the metaproteome level.…”
Section: Discussionmentioning
confidence: 99%
“…Current research is strongly guided by evidence of the existence of different cellular physiological states that marine bacteria display under variable environmental conditions (Kaprelyants et al, 1996;Comas & Vives-Rego, 1998;Fegatella & Cavicchioli, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these physiotypes, it may be expected that oligotrophic Bacteria would have relatively few changes in gene expression in comparison with their copiotrophic counterparts. This, however, is not the case as it has been shown that starvation of S. alaskensis produces a high level of change in gene expression (Fegatella and Cavicchioli, 2000). Importantly, the capacity of this organism to display a distinct starvation response could be rationalized with the ecology of its native environment.…”
Section: Searching For Extraterrestrialsmentioning
confidence: 85%